2004
DOI: 10.1519/r-12972.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Direct Supervision of a Strength Coach on Measures of Muscular Strength and Power in Young Rugby League Players

Abstract: ABSTRACT. Coutts, A.J., A.J. Murphy, and B.J. Dascombe. Effect of direct supervision of a strength coach on measures of muscular strength and power in young rugby league players. J. Strength Cond. Res. 18(2):316-323. 2004.-The purpose of the present study was to examine the influence of direct supervision on muscular strength, power, and running speed during 12 weeks of resistance training in young rugby league players. Two matched groups of young (16.7 Ϯ 1.1 years [mean Ϯ SD]), talented rugby league players c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
42
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 28 publications
4
42
0
1
Order By: Relevance
“…A significant correlation existed between sessions completed and change in strength levels, not surprising considering only 32.5% of prescribed workouts were completed and training intensity reduced by approximately 30% from typical supervised training (3). Even when unsupervised compliance rates and training volume are high, a number of key physiological variables may not improve or even succumb to reversibility if inadequate frequency, volume, or intensity of training takes place.…”
Section: Training Supervisionmentioning
confidence: 99%
See 4 more Smart Citations
“…A significant correlation existed between sessions completed and change in strength levels, not surprising considering only 32.5% of prescribed workouts were completed and training intensity reduced by approximately 30% from typical supervised training (3). Even when unsupervised compliance rates and training volume are high, a number of key physiological variables may not improve or even succumb to reversibility if inadequate frequency, volume, or intensity of training takes place.…”
Section: Training Supervisionmentioning
confidence: 99%
“…It has been suggested that direct supervision increased training intensity and rate of adaptation to a strength program, whereas lack of supervision resulted in inadequate workout quality (3). This increased intensity appears to be facilitated by coaches and enhanced by increased motivation, sense of safety, and competitiveness at training.…”
Section: Training Supervisionmentioning
confidence: 99%
See 3 more Smart Citations